Modeling of the deactivation kinetics for the combustion of ethyl acetate and benzene present in the air stream over ZSM-5. catalyst loaded with chromium - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (Elsevier, 2004)

(untitled)
Deactivation kinetics of chromium exchanged ZSM-5 (Cr-ZSM-5.Si/Al:240)catalyts by coking during the combustion of ethyl acetate (EAc) and benzene (Bz) present in the air stream is reported.